2020
DOI: 10.1590/1980-549720200093
|View full text |Cite
|
Sign up to set email alerts
|

Desigualdades de renda e capacidade funcional de idosos em município do Sudeste brasileiro

Abstract: RESUMO: Objetivo: Estimar a magnitude das desigualdades de renda nas prevalências de dependência funcional em atividades básicas e instrumentais da vida diária (ABVDs e AIVDs, respectivamente) e no abandono de atividades avançadas (AAVDs). Métodos: Estudo transversal, de base populacional, desenvolvido com dados de amostra de 986 idosos de inquérito de saúde realizado no município de Campinas, São Paulo, em 2014/15. Foram estimadas as prevalências de dependência funcional em ABVDs e AIVDs e de abandono das… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
2
1
4
Order By: Relevance
“…The results show an overall prevalence rate of functional limitations in at least one BADL of the 21% and disaggregated by sexes was 24% for women and 17% for men. This prevalence is increased regarding the previous 16% from 2013-PNS; however, it must be noted that this study considered just six BADLs [34] and higher than that observed in a previous study carried out in Brazil by Veloso et al considering five BADLs in a sample data of 986 people aged 60 years or over from municipality of Campinas, São Paulo in 2014/15, shows a prevalence of 8.4% [35]. Thus, the differences in prevalence between studies depend on the functional health limitations of the target populations and methodological aspects such as type of instruments for assessing functional health or the number of BADLs analyzed; thus, comparability of the findings of this study with others is limited.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…The results show an overall prevalence rate of functional limitations in at least one BADL of the 21% and disaggregated by sexes was 24% for women and 17% for men. This prevalence is increased regarding the previous 16% from 2013-PNS; however, it must be noted that this study considered just six BADLs [34] and higher than that observed in a previous study carried out in Brazil by Veloso et al considering five BADLs in a sample data of 986 people aged 60 years or over from municipality of Campinas, São Paulo in 2014/15, shows a prevalence of 8.4% [35]. Thus, the differences in prevalence between studies depend on the functional health limitations of the target populations and methodological aspects such as type of instruments for assessing functional health or the number of BADLs analyzed; thus, comparability of the findings of this study with others is limited.…”
Section: Discussioncontrasting
confidence: 72%
“…Bof de Andrade et al (2018) with a nationally representative sample of adults aged 50 years or older indicated that inequalities in BADLs limitation are primarily explained by socioeconomic status (wealth and own education), not by demographic or health factors [38]. On the other hand, Veloso et al does not found a significant association between dependence on 5-BADLs and family income [35].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that no studies were identified in the scientific literature that assessed the mediating role of participation in AADL in the association between these variables. However, research developed in southeastern Brazil (28) and in other regions (29) found that older adults with low income had lower participation in AADL (28)(29) . This result may be related to the fact that older adults with lower income generally reside in more socially vulnerable areas (30) and, therefore, have less participation in social activities, such as AADL, due to restricted access in these areas to services for the community and, above all, due to sanitary and urban infrastructure limitations in these locations (31) .…”
Section: Discussionmentioning
confidence: 99%
“…Destaca-se que não foram identificadas, na literatura científica, pesquisas que avaliaram o papel mediador da participação nas AAVD na associação entre essas variáveis. Contudo, pesquisas desenvolvidas na região Sudeste do Brasil (28) e em outras regiões (29) verificaram que idosos com baixa renda tiveram menor participação nas AAVD (28)(29) . Tal resultado pode estar relacionado ao fato de os idosos com menor renda, geralmente, residirem em áreas mais vulneráveis socialmente (30) e, portanto, apresentarem menor participação em atividades sociais, como as AAVD, devido ao acesso restrito nessas áreas a serviços para a comunidade e, sobretudo, pelas limitações sanitárias e de infraestrutura urbana nessas localidades (31) .…”
Section: Discussionunclassified